Innovative Governance dalam Pengelolaan Desa Digital (Studi Kasus: Desa Punggul, Kecamatan Abiansemal, Kabupaten Badung) - Sari, Ni Putu Mirna; Supriliyani, Ni Wayan; Yudharta, I Putu Dharmanu (CITIZEN CHARTER, 2022)
Punggul Village is one of the villages that is aggressively innovating by utilizing technology. Their success in innovations makes Punggul Village earn the title of Digital Village. However, its management has several problems, such as public awareness, organizational culture, human resources, finance, and system management. This study aims to determine the implementation of Innovative Governance in Digital Villages Management at Punggul Village. This research uses the Innovative Governance theory from UN-Habitat in Sangkala (2014). Using the descriptive qualitative method, data were collected through interviews, observations, and documentation analyzed by the Miles and Huberman model. The results indicate that Punggul Digital Village can be categorized as Innovative Governance. However, Punggul Village needs to improve several things, especially on indicators of partnership and leadership-community empowerment. These problems can be resolved by increasing the number of human resources and a more in-depth study of village problems. Keywords: Digital Village, Innovative Governance, Management